The castle of perseverance - Klausner, David N. (Middle English texts (Kalamazoo, Mich.), 2010)
The play deals allegorically with the life of man and his struggle against sin, and the structure is for the most part based on a sequence of temptation, fall and redemption. The play describes the whole ontology of man, opening before his birth and ending after his death and his judgment before the throne of God. The volume includes an introduction, textual and explanatory notes, a bibliography and a glossary.